Analisis Periodisitas Gempa Bumi Diwilayah Kabupaten Lombok Barat Dengan Menggunakan Metode Statistik Dan Transformasi Wavelet: Fatimatuzzahra Fatimatuzzahra, Lalu A. Didik, Bahtiar Bahtiar - Fatimatuzzahra Fatimatuzzahra Fatimatuzzahra Fatimatuzzahra; Lalu A. Didik Lalu A. Didik; Bahtiar Bahtiar (Jurnal Fisika dan Aplikasinya, 2020)
This research is experimental research. Where the aim is to find out the first variotion of the a- vuale and the –b vuale, the second is to know the earthquake frequency whit the statistical method and wavelet transformation. And the third to analyze the results of the statistical method and wavelet transformation in the west Lombok regency. The method used to determine the earthquake periodicity in the study is the statistical method and the wavelet transformation. Statistical methods with Zmap sofwer are used to determine –a values, -b vuales, and earthquake periodicity. The wavelet transformation method uses skeweness, Box Cox transformation, and continyu wavelet transformation to calculate earthquake periodicity. This study uses data from BMKG and the National Earthquake International Center (NIEC) for the area between the epicenter of 1150.46-1160.20 BT, and 80.25 to 80.55 LS from 22 January 2014 to 30 October 2018. Statistical analysis produces parameters related to saismic conditions (seismic) and tectonic research area. The parameter consists of a vuale –a around 5,5 – 2 the –b vuale of 0,9 – 1,8. Both of these parameters shwo a rare earthquake and quite high stress on the plate. Periodicity based on the results of statistical analysis is around 40-60 years for magnitude 5,5 SR. with the wavelet transformation method, the periodecity of 30 years and 60 years is obtained for earthquakes with magnitude 5,5 SR. these results indicate that the two methods produce almost the same periodecity values.